Types of classifier in artificial intelligence (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Artificial intelligence or machine intelligence should be considered as the vast domain of junction of many knowledge, sciences and old and new technics. Today, classification of documents is adopted extensively in information recovery for organizing documents. In the method of document supervised classification some correct information about documents that previously have been classified are available for us and based on these information we classify these documents. Thus, we will examine methods such as: expert systems, artificial neural network, Genetic algorithm and fuzzy logics and so on. In this project we examine documents thematically and then using existing algorithms we predict a theme for a new document.